STRATEGI PT. KIA MARINDO JUSEMA JAKARTA DALAM MENANGANI KESIAPAN CREW PADA KAPAL BENDERA KOREA SELATAN - Hidayat, Rahmat; Asih, Estri Wahyuning; Nasrulloh, Nasrulloh (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of the study is to figure out the internal and external factors related to the strength and weaknes in preparing the crew. The method used was field and library research by observing, interviewing, and spreading questionnaire. SWOT analysis was used to analyse the data. The internal factor of PT. Kia Marindo Jusema Jakarta has more strength than the weakness factor. The dominant strength lies in professional human resource service of 0.67. The weakness is found in the lack of the crew document of 0.24. The external factor of the company has more opportunity than threat. The most dominant opportunity factor is the increasing need of crew ship of 0.76 while the most dominant threat factor is the lack of qualified crew needed by the company of 0.31. The steps taken to minimize the internal weakness and face the external threat are by building cooperation with crew ship certified institution approved by Indonesia ministry of transportation to deal with the lack of certified crew document and expanding cooperation with sailor / crew ship communities and private shipping academy in Indonesia to deal with the lack of certified crew ship.